A maximum rupture model for the central and southern Cascadia subduction zone—reassessing ages for coastal evidence of megathrust earthquakes and tsunamis - Nelson, Alan R.; DuRoss, Christopher B.; Witter, Robert C.; Kelsey, Harvey M.; Engelhart, Simon E.; Mahan, Shannon A.; Gray, Harrison J.; Hawkes, Andrea D.; Horton, Benjamin P.; Padgett, Jason S. (Quaternary Science Reviews, 2021)
A new history of great earthquakes (and their tsunamis) for the central and southern Cascadia subduction zone shows more frequent (17 in the past 6700 yr) megathrust ruptures than previous coastal chronologies. The history is based on along-strike correlations of Bayesian age models derived from evaluation of 554 radiocarbon ages that date earthquake evidence at 14 coastal sites. We reconstruct a history that accounts for all dated stratigraphic evidence with the fewest possible ruptures by evaluating the sequence of age models for earthquake or tsunami contacts at each site, comparing the degree of temporal overlap of correlated site age models, considering evidence for closely spaced earthquakes at four sites, and hypothesizing only maximum-length megathrust ruptures. For the past 6700 yr, recurrence for all earthquakes is 370e420 yr. But correlations suggest that ruptures at-1.5 ka and-1.1 ka were of limited extent (<400 km). If so, post-3-ka recurrence for ruptures extending throughout central and southern Cascadia is 510e540 yr. But the range in the times between earthquakes is large: two instances may be-50 yr, whereas the longest are-550 and-850 yr. The closely spaced ruptures about 1.6 ka may illustrate a pattern common at subduction zones of a long gap ending with a great earthquake rupturing much of the subduction zone, shortly followed by a rupture of more limited extent. The ruptures of limited extent support the continued inclusion of magnitude-8 earthquakes, with longer ruptures near magnitude 9, in assessments of seismic hazard in the region.

Holocene earthquake history and slip rate of the southern Teton fault, Wyoming, USAAbstract - DuRoss, Christopher B.; Gold, Ryan D.; Briggs, Richard W.; Delano, Jaime E.; Ostenaa, Dean A.; Zellman, Mark S.; Cholewinski, Nicole; Wittke, Seth J.; Mahan, Shannon A. (GSA Bulletin, 2020)
The 72-km-long Teton normal fault bounds the eastern base of the Teton Range in northwestern Wyoming, USA. Although geomorphic surfaces along the fault record latest Pleistocene to Holocene fault movement, the postglacial earthquake history of the fault has remained enigmatic. We excavated a paleoseismic trench at the Buffalo Bowl site along the southernmost part of the fault to determine its Holocene rupture history and slip rate. At the site, ∼6.3 m of displacement postdates an early Holocene (ca. 10.5 ka) alluvial-fan surface. We document evidence of three surface-faulting earthquakes based on packages of scarp-derived colluvium that postdate the alluvial-fan units. Bayesian modeling of radiocarbon and luminescence ages yields earthquake times of ca. 9.9 ka, ca. 7.1 ka, and ca. 4.6 ka, forming the longest, most complete paleoseismic record of the Teton fault. We integrate these data with a displaced deglacial surface 4 km NE at Granite Canyon to calculate a postglacial to mid-Holocene (14.4–4.6 ka) slip rate of ∼1.1 mm/yr. Our analysis also suggests that the postglacial to early Holocene (14.4–9.9 ka) slip rate exceeds the Holocene (9.9–4.6 ka) rate by a factor of ∼2 (maximum of 3); however, a uniform rate for the fault is possible considering the 95% slip-rate errors. The ∼5 k.y. elapsed time since the last rupture of the southernmost Teton fault implies a current slip deficit of ∼4–5 m, which is possibly explained by spatially/temporally incomplete paleoseismic data, irregular earthquake recurrence, and/or variable per-event displacement. Our study emphasizes the importance of minimizing slip-rate uncertainties by integrating paleoseismic and geomorphic data sets and capturing multiple earthquake cycles.

Holocene Rupture History of the Central Teton Fault at Leigh Lake, Grand Teton National Park, WyomingABSTRACT - Zellman, Mark S.; DuRoss, Christopher B.; Thackray, Glenn D.; Personius, Stephen F.; Reitman, Nadine G.; Mahan, Shannon A.; Brossy, Cooper C. (Bulletin of the Seismological Society of America, 2020)
Prominent scarps on Pinedale glacial surfaces along the eastern base of the Teton Range confirm latest Pleistocene to Holocene surface‐faulting earthquakes on the Teton fault, but the timing of these events is only broadly constrained by a single previous paleoseismic study. We excavated two trenches at the Leigh Lake site near the center of the Teton fault to address open questions about earthquake timing and rupture length. Structural and stratigraphic evidence indicates two surface‐faulting earthquakes at the site that postdate deglacial sediments dated by radiocarbon and optically stimulated luminescence to ∼10–11  ka⁠. Earthquake LL2 occurred at ∼10.0  ka (9.7–10.4 ka; 95% confidence range) and LL1 at ∼5.9  ka (4.8–7.1 ka; 95%). LL2 predates an earthquake at ∼8  ka identified in the previous paleoseismic investigation at Granite Canyon. LL1 corresponds to the most recent Granite Canyon earthquake at ∼4.7–7.9  ka (95% confidence range). Our results are consistent with the previously documented long‐elapsed time since the most recent Teton fault rupture and expand the fault’s earthquake history into the early Holocen

Four Major Holocene Earthquakes on the Reelfoot Fault Recorded by Sackungen in the New Madrid Seismic Zone, USA - Gold, Ryan D.; DuRoss, Christopher B.; Delano, Jaime E.; Jibson, Randall W.; Briggs, Richard W.; Mahan, Shannon A.; Williams, Robert A.; Corbett, D. Reide (Journal of Geophysical Research: Solid Earth, 2019)
Three sequences of well‐documented, major ~M7+ earthquakes (1811–1812, ~1450, and ~900 CE) in the New Madrid seismic zone, USA, contribute significantly to seismic hazard in the region. However, it is unknown whether this <550‐year recurrence interval has been constant throughout the Holocene given limited geomorphic evidence of prior earthquakes. We extend the record of paleoearthquakes along the Reelfoot fault via investigation of ridgetop gravitational failure features, interpreted as sackungen. The sackungen occur in bluffs along the eastern margin of the Mississippi River floodplain and are concentrated near (<15 km) the southwest dipping Reelfoot reverse fault. A paleoseismic trench excavated across sackungen at the Paw Paw site exposed four packages of colluvial sediment that postdate 30‐ to 11‐ka Peoria Loess. We interpret the colluvial packages to have been deposited following episodic failure of the sackungen as a result of strong ground motions from the following sequence of earthquakes: event 4, 1640 ± 1730 BCE; event 3, 270 ± 670 CE; event 2, 1430 ± 380 CE; and event 1, 1810 ± 50 CE (2 sigma). Event timing corresponds to previously documented earthquakes and represents the longest archive of paleoearthquakes on the Reelfoot fault. If the trenched sackungen record all major Reelfoot fault earthquakes, our observations in combination with prior investigations indicate a period of quiescence from at least 11 to 4.4 ka, followed by four major seismic events culminating in the 1811–1812 CE sequence. This clustered earthquake recurrence pattern helps place bounds on seismic hazard and geodynamic models in the New Madrid seismic zone.

Combining Conflicting Bayesian Models to Develop Paleoseismic Records: An Example from the Wasatch Fault Zone, Utah - DuRoss, Christopher B.; Bennett, Scott E. K.; Briggs, Richard W.; Personius, Stephen F.; Gold, Ryan D.; Reitman, Nadine G.; Hiscock, Adam I.; Mahan, Shannon A. (Bulletin of the Seismological Society of America, 2018)
Bayesian statistical analyses of paleoseismic data result in the probabilistic determination of earthquake times using geochronological data evaluated in the context of a stratigraphic model. However, a fundamental problem in paleoseismology is how to use the Bayesian approach to model sparse and/or conflicting geochronological datasets, such as those derived from sites exhibiting episodic sedimentary and pedogenic processes in moderate‐ to high‐energy environments (e.g., a normal‐faulted alluvial fan). Using paleoseismic data for the Corner Canyon site on the Salt Lake City segment of the Wasatch fault zone (Utah), we develop an approach by which multiple Bayesian models are combined to generate an earthquake history at a site. This approach accommodates mutually exclusive interpretations of the geochronological data and thereby limits the influence of sparse data, stratigraphically inconsistent ages, or a single, subjective model interpretation. For the Corner Canyon site, we integrate four OxCal Bayesian models to generate a chronology of six events between ∼4.8 and ∼0.5  ka. Late Holocene (post‐5 ka) mean recurrence and vertical slip‐rate estimates are ∼0.9  ky (0.7–1.0 ky; 95% confidence) and 1.1  mm/yr (0.8–1.7  mm/yr range), respectively. Although our method increases the uncertainty in the timing of individual earthquakes, it more objectively accounts for potential geochronological errors and different interpretations of stratigraphic age control. By relaxing the need to select a single age model, our approach yields more accurate earthquake‐timing results that will better facilitate evaluations of along‐fault event correlation and earthquake rupture length.

Moderate rates of late Quaternary slip along the northwestern margin of the Basin and Range Province, Surprise Valley fault, northeastern California - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Lidke, David J. (Journal of Geophysical Research-Solid Earth, 2009)
The 86-km-long Surprise Valley normal fault forms part of the active northwestern margin of the Basin and Range province in northeastern California. We use trench mapping and radiocarbon, luminescence, and tephra dating to estimate displacements and timing of the past five surface-rupturing earthquakes on the central part of the fault near Cedarville. A Bayesian OxCal analysis of timing constraints indicates earthquake times of 18.2 +/- 2.6, 10.9 +/- 3.2, 8.5 +/- 0.5, 5.8 +/- 1.5, and 1.2 +/- 0.1 ka. These data yield recurrence intervals of 7.3 +/- 4.1, 2.5 +/- 3.2, 2.7 +/- 1.6, and 4.5 +/- 1.5 ka and an elapsed time of 1.2 +/- 0.1 ka since the latest surface-rupturing earthquake. Our best estimate of latest Quaternary vertical slip rate is 0.6 +/- 0.1 mm/a. This late Quaternary rate is remarkably similar to long-term (8-14 Ma) minimum vertical slip rates (>0.4-0.5 +/- 0.3 mm/a) calculated from recently acquired seismic reflection and chronologic and structural data in Surprise Valley and the adjacent Warner Mountains. However, our slip rate yields estimates of extension that are lower than recent campaign GPS determinations by factors of 1.5-4 unless the fault has an unusually shallow (30 degrees-35 degrees) dip as suggested by recently acquired seismic reflection data. Coseismic displacements of 2-4.5 +/- 1 m documented in the trench and probable rupture lengths of 53-65 km indicate a history of latest Quaternary earthquakes of M 6.8-7.3 on the central part of the Surprise Valley fault.
id: 2021; PT: J; UT: WOS:000270058200001

Late quaternary paleoseismology of the southern Steens fault zone, northern Nevada - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Kyung, Jai Bok; Cisneros, Hector; Lidke, David J. (Bulletin of the Seismological Society of America, 2007)
The 192-km-long Steens fault zone is the most prominent normal fault system in the northern Basin and Range province of western North America. We use trench mapping and radiometric dating to estimate displacements and timing of the last three surface-rupturing earthquakes (E1-E3) on the southern part of the fault south of Denio, Nevada. Coseismic displacements range from 1.1 to 2.2 +/- 0.5 m, and radiometric ages indicate earthquake times of 11.5 +/- 2.0 ka (E3), 6.1 +/- 0.5 ka (E2), and 4.6 +/- 1.0 ka (E1). These data yield recurrence intervals of 5.4 +/- 2.1 k.y. between E3 and E2, 1.5 +/- 1.1 k.y. between E2 and E1, and an elapsed time of 4.6 +/- 1.0 k.y. since El. The recurrence data yield variable interval slip rates (between 0.2 +/- 0.22 and 1.5 +/- 2.3 mm/yr), but slip rates averaged over the past similar to 18 k.y. (0.24 +/- 0.06 mm/year) are similar to long-term (8.5-12.5 Ma) slip rates (0.2 +/- 0.1 mm/yr) measured a few kilometers to the north. We infer from the lack of significant topographic relief across the fault in Bog Hot Valley that the fault zone is propagating southward and may now be connected with a fault at the northwestern end of the Pine Forest Range. Displacements documented in the trench and a rupture length of 37 km indicate a history of three latest Quaternary earthquakes with magnitudes of M 6.6-7.1 on the southern part of the Steens fault zone.
id: 2022; PT: J; UT: WOS:000249930900021